Experimental Study on the Influence of TiN/AlTiN PVD Layer on the Surface Characteristics of Hot Work Tool Steel - Enikő Bitay; László Tóth; Tünde Anna Kovács; Zoltán Nyikes; Attila Levente Gergely (Applied Sciences, 2021)
It is desirable to improve tool steel wear resistance to produce pieces with precise dimensions and increase the lifetime of tools. The aim of this work was to modify the surface of 1.2344 (X40CrMoV5-1) hot work tool steel to improve the wear properties. Surface modification was achieved in three steps: first, hardening was applied, followed by plasma nitridation and, finally, physical vapor deposition (PVD) was employed to produce a TiN/AlTiN multilayer coating. The microhardness and the wear coefficient of the surfaces were measured. PVD coating showed the highest hardness value, 2938 HV0.01, whereas plasma nitridation followed by PVD resulted in 2679 HV0.01. The surface modification resulted in an increase in surface roughness in all cases compared to the hardened sample. However, the wear coefficient showed a significant decrease for the surface treated samples. The lowest wear coefficient of K = 1.47 × 10−10 mm3/Nm, which is a magnitude lower than the reference hardened sample (K = 6.32 × 10−9 mm3/Nm), was achieved employing both plasma nitridation and PVD. The results confirm that the use of a combined surface modification of plasma nitridation and PVD significantly improve the wear resistance of the treated samples.